2011
DOI: 10.1111/j.1749-124x.2011.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Economic Growth in China: An Empirical Analysis

Abstract: Using official provincial data for gross provincial product, consumer price index and other explanatory variables from 1986 to 2006, the present paper investigates the nonlinear effects of inflation on economic growth in China. The main finding of the study is that the inflation threshold effect is highly significant and robust in China. Above the 2.50 percent threshold, every 1‐percentage point increase in the inflation rate impedes economic growth by 0.61 percent; below this threshold, every 1‐percentage poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…While inflation showed negative linkage with economic growth for China. Hwang and Wu (2011) indicate that increasing is damaging for economic growth whereas moderate inflation benefits growth in case of China. They concluded that every one percentage rise in inflation rate impedes economic growth by 0.61 percent.…”
Section: Datamentioning
confidence: 99%
“…While inflation showed negative linkage with economic growth for China. Hwang and Wu (2011) indicate that increasing is damaging for economic growth whereas moderate inflation benefits growth in case of China. They concluded that every one percentage rise in inflation rate impedes economic growth by 0.61 percent.…”
Section: Datamentioning
confidence: 99%
“…In conclusion, in China, over 20 years, high inflation had a negative influence on economic growth, while moderate inflation favored economic growth. The study's recommendation is that a moderate inflation rate should be maintained for long-term growth (Hwang and Wu, 2011). Otoiu (2014) analysed migration at EU's level between 2000 and 2007, using panel data, and concluded that most of the models and variables used in migration analysis are valid for international migration.…”
Section: Methodsmentioning
confidence: 99%
“…This has led to the emergence of a small number of papers that adopt non-linear estimation techniques to examine Chinese inflation. Hwang & Wu (2011) examine the nonlinear effect of inflation on economic growth and conclude that high inflation harms economic growth, whereas moderate inflation benefits growth. Zhang (2013) models Chinese inflation using a four-regime logistic smooth transition autoregressive model and finds that the effect of shocks to price levels is transient and asymmetrical.…”
Section: Introductionmentioning
confidence: 99%